2017
DOI: 10.1080/15389588.2017.1310380
|View full text |Cite
|
Sign up to set email alerts
|

Concept of an enhanced V2X pedestrian collision avoidance system with a cost function–based pedestrian model

Abstract: Objective: State-of-the-art collision avoidance and collision mitigation systems predict the behavior of pedestrians based on trivial models that assume a constant acceleration or velocity. New sources of sensor information-for example, smart devices such as smartphones, tablets, smartwatches, etc.-can support enhanced pedestrian behavior models. The objective of this article is the development and implementation of a V2Xpedestrian collision avoidance system that uses new information sources. Methods: A litera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…It could be too late for drivers to take evasive actions when the pedestrian was already in the FOV. Thus, more work should be done to capture and predict pedestrians’ jaywalking intentions ( 14 , 15 ).…”
mentioning
confidence: 99%
“…It could be too late for drivers to take evasive actions when the pedestrian was already in the FOV. Thus, more work should be done to capture and predict pedestrians’ jaywalking intentions ( 14 , 15 ).…”
mentioning
confidence: 99%
“…It has to be mentioned that the majority of the authors tried to tackle non-line-of-sight and blind spots, where the driver's view is limited due to buildings, vehicles and other obstacles. The majority of research was carried out in 2014 [14,[19][20][21], in 2016 [1,[22][23][24][25][26] and in 2017 [27][28][29]. Moreover, most of the V2P developments used several sensors data fusion techniques [1,19,21,22,24,26,27,30], while some of them [20,31] discussed methods to predict VRU next move/short path and some others presented collision avoidance systems [23,26,32].…”
Section: Vehicle To Pedestrians (V2p) Systems-developmentsmentioning
confidence: 99%
“…However, the previously proposed systems still have some limitations in identifying pedestrians' intended crossing behaviors, because it is difficult for the distance sensors to capture characteristics of pedestrians such as age and gender. These contributing factors are deeply correlated with the speed and acceleration of the pedestrian who is crossing (9,10). Several previous studies also revealed that information on the pedestrian's head orientation has a high potential for being useful for recognizing the pedestrian's decision to cross the road or not (10)(11)(12).…”
mentioning
confidence: 99%
“…These contributing factors are deeply correlated with the speed and acceleration of the pedestrian who is crossing (9,10). Several previous studies also revealed that information on the pedestrian's head orientation has a high potential for being useful for recognizing the pedestrian's decision to cross the road or not (10)(11)(12). Consequently, such characteristics of pedestrians highly affect the performance of ICWS in preventing pedestrian-vehicle collisions caused by the unexpected hazardous behaviors of pedestrians crossing (13)(14)(15).…”
mentioning
confidence: 99%
See 1 more Smart Citation